Landschaftsökologische Studien im südniedersächsischen Bergland - Klink, Hans-Jürgen (ERDKUNDE, 1964)
The paper deals with the ecological micro-structure of some small regional units (morphographical units) of the hill country of southern Lower Saxony. The following examples of this scarp-crest and cuesta region respectively are dealt with: 1st Remnant mountains of the Plan limestone scarps (kro 1 and 2) in the centre of the Vale of Hils, 2nd Separated mountains of the fairly regularly dissected Flammen marl (kru 2 y) scarp, also within this vale, 3rd Badly drained shallow depressions on the Muschel kalk (shelly limestone) plateau (mo2) of the Göttinger Wald. The ecological micro-structure of the vegetation within each of these morphographic units depends in turn on different factors of organisation. They are for the remnant hills of the Plan limestone scarp (central witness mountains) of the vale of Hils: the relief in mutual rela tionship with differing degrees of erosional force depending on slope aspect and the topo-climates which also depend greatly on aspect. At the separated mountains of the dissected scarp of the Flammen marl the detailed plant-ecological structure is mainly the result of relief conditions in conjunction with the different parent materials of soils. Superimposed on these two factors of organisation are the topo-climates which largely depend on slope aspect. The ecological conditions within the consequent valleys are, however, the result of the distance of the ground water table from the surface - which in turn determines the water regime of the soil - and of the kind of ground water movement. An additional modifying factor is here also the topo-climate which changes according to the strike of the dissected scarp. In the badly drained ecotops of the Ceratitenkalk plateau of the Gottinger Wald the distribu tion pattern of the different soil types and plant associations is conditioned by the degree of water logging which in turn depends on micro-relief and base rocks. Thus the ecological variation within the morphographic units according to relief depends in the first place on these factors, though further geo-factors also play their role.